The Impact of the Flipped Classroom Model of Instruction on the Reading Achievement of Ninth Grade Female Emirati students in the Qurtoba Public School in Dubai - Khadragy, Saada Abdelgawad Mohamed (2016)
This research study examines the effect of the Flipped Classroom Model of Instruction (FCMI) method of teaching on the reading achievement of ninth grade Emirati female students at the Qurtoba Public School in Dubai, United Arab Emirates (UAE). The present study sought to determine if there are any real differences in the reading achievement of students who had FCMI classes and students taught with the teacher-centred method. The research also aims to measure the influence of the main variable on the different levels of students according to their ESL reading diagnostic test. The duration of the experiment was about eight weeks and covered eighteen reading lessons. Fifty-five students were put into two groups (the experimental and the control group). As the method of teaching was intended to be the main variable, instructional videos were designed for the experimental group only, while the control group was taught face to face in the usual way with what might be characterized as a student-centered approach. The main instrument of this research is the pre- and the post-test together with a diagnostic test that was administered to all individuals in both groups. This was done in order to divide students in the experimental group into three different levels based on their level of competency and to determine the participants with the poorest skills with the lowest scores for both the experimental and the control groups. In addition to the assigned pre-test which included an overview to explore the levels of students and the starting point of the program with an illustration to their reading abilities. Three themes of the ESL textbook containing xii eighteen lessons formed the program materials. Instructional videos were prepared for the experimental group while the control group had their lessons administered in the classrooms. After the allocated time of the treatment, the post-test was administered to the two groups. The results of both the pre- and the post-tests were recorded on an Excel sheet and analysed by the researcher. The results of the study showed that there were statistical differences between the two groups’ marks the post-test. Furthermore, the results showed that the high achiever students were more affected by the program than the other levels. The results showed the significant effect of the FCMI teaching method on teaching ESL reading skills.